Nutraceuticals: An inspiring therapy for lifestyle diseases - Snigdha Bhardwaj; Prakhar Kunj; Shalini Sharma (German Journal of Pharmaceuticals and Biomaterials, 2023)
Among natural sources, majorly we consider plant-based phytochemicals to offer safe and longlasting effects. Phytochemicals or secondary metabolites are the extract obtained from herbal plants that serve as an excellent venture for their utilization as formulation. Different nutraceuticals (herbal formulations) have always been a part of the world. Everyone around the world could use these supplements for their benefit. Since the end of the eighth century and the beginning of the nineteenth century, the concept of using products has improved. Nutraceutical food supplement plays an essential role for humans to stay healthy and gets all the important nutrients used for the body's basic metabolism and further prevent all kinds of illnesses. The present review highlights the potential of nutraceuticals against various types of leading life-threatening disorders such as diabetes, obesity, asthma, cardiac conditions, arthritis, cancer, etc. This review focuses on the nutraceuticals that help manage certain many life-threatening disorders.